Analytical model of the eddy current response of a drive-receive coil system inside two concentric tubes. (June 2018) - Klein, Geoffrey; Morelli, Jordan; Krause, Thomas W.
Abstract: A semi-analytical model of the eddy current response of a drive-receive coil configuration inside two conducting concentric tubes, where the coil axes are perpendicular to the inner tube's surface, is solved using the second-order vector potential formalism. This model determines the voltage response in the receive coil under a constant amplitude alternating drive voltage, accounting for all possible coupling terms in the system. Modeled receive coil voltage responses to changes in outer tube diameter, greater than the drive-receive coil spacing, are compared with experimental measurements and finite element method (FEM) modeling in the impedance plane. Analytical model results are found to be in excellent agreement with both experiment and FEM model results, thereby verifying the solutions. Highlights: Analytical model of drive-receive coil inside two concentric tubes is presented. Model utilizes the Second Order Vector Potential formalism. Voltage excitation in drive coil properly accounts for all feedback effects. Voltage response of receive coil shows excellent agreement with measurements.